2012
DOI: 10.1111/j.1911-3838.2012.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Constructive Lease Capitalization and Off‐Balance‐Sheet Financing: An Instructional Case with FedEx and UPS

Abstract: This case illustrates the effects of the proposed new lease standard by the Financial Accounting Standards Board and the International Accounting Standards Board on existing outstanding operating leases. Specifically, the case examines the effects of the proposal that all firms report existing operating leases as capital leases upon the initial adoption of the proposed standard. By applying a constructive capitalization model to two firms who rely on operating leases for financing, FedEx and UPS, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Imhoff et al (1991) estimated the unexpired lease term as 50 per cent of the total lease term. This estimation is accepted by Bennett and Bradbury (2003), Duke and Hsieh (2006), Duke et al (2009 and2012). However, many others consider firm-specific factors to calculate the weighted, average, remaining lease term and total lease term (Beattie et al, 1998;Goodacre, 2003;Lückerath-Rovers and de Bos, 2005).…”
Section: Converting Financial Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imhoff et al (1991) estimated the unexpired lease term as 50 per cent of the total lease term. This estimation is accepted by Bennett and Bradbury (2003), Duke and Hsieh (2006), Duke et al (2009 and2012). However, many others consider firm-specific factors to calculate the weighted, average, remaining lease term and total lease term (Beattie et al, 1998;Goodacre, 2003;Lückerath-Rovers and de Bos, 2005).…”
Section: Converting Financial Statementsmentioning
confidence: 99%
“…Imhoff et al (1991) used 70 per cent and later used 75 per cent (Imhoff et al, 1997). Others followed Imhoff et al (1991) with 70 per cent (Duke et al, 2012(Duke et al, , 2009Duke and Hsieh, 2006), while Bennett and Bradbury (2003) used 81 per cent. However, the present value of unrecorded leased assets can be specified with more accuracy for each company as long as three elements (present value of lease commitments, total lease term and unexpired lease term) are determined.…”
Section: Converting Financial Statementsmentioning
confidence: 99%
“…The results of the study also match the viewpoints of Graham and King (2011), who found that the right-to-use leased asset value is strongly associated with current and future return on assets. Duke et al (2012) also suggested that the firms would experience a decline in retained earnings and key financial ratios, such as the debt-to-equity, return-on-assets, and interest coverage ratios, by reporting operating leases as capital leases under the new proposed standard.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…The arguments for effects of leasing on the financial performance of a company have focused mainly on four elements including tax differential, debt substitutability, agency costs and free cash flows. Duke et al (2012) studied the effect of the proposed new lease standard by the Financial Accounting Standards Board and the International Accounting Standards Board on existing outstanding operating leases. Specifically, the case examined the effect of the proposal that all firms report existing operating leases as capital leases upon the initial adoption of the proposed standard.…”
Section: Empirical Reviewmentioning
confidence: 99%